Physiological regulation and environmental harmfulness: bioethical aspects of scientific metaphores - Lolas Stepke, Fernando (Acta Bioethica, 2001)
This article examines historically the social influence of scientific physiology as the foundation of medicine and the tension between cosmopolitan and universal science and particular daily contexts. These tension is traced back to the machine metaphor, central in nineteenth century physiology, modified by the human and social sciences, which introduce "historicity" (as different from mere temporality) as a modifying factor. Physiological regulations find limits of application in social medicine, in the development of standards in work and sports and in the assessment of environmental harmfulness. Discursive construction of implicit metaphors is proposed as a means for establishing a dialogue between rationalities and persons, thus permitting bioethical deliberation.